AppMatetics as a support for the learning of algebraic operations in University students - Salazar-Gómez, Julio Fernando; Dolores-Ruíz, Erika; Vázquez-Cruz, Rafael; Tejeda-Córdoba, Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The purpose of this article is to evaluate the effect of an application for mobile devices, developed for the learning of algebraic operations in university students. The research has a correlational quantitative approach, with a pre- and post-test experimental design in two groups. The experimental group used the AppMatetics application, designed for Android devices, for three weeks. The sample consisted of 196 first-semester students, belonging to a Mexican educational institution, who were divided into two groups using the matching method. In the post-test, the experimental group had a mean score of 3.87, while the control group had a mean of 2.97. The p was 0.034, less than 0.05, which indicates that there was a significant difference in the scores of the experimental and control groups. It is concluded that the users of the AppMatetics software had a better performance than those who did not use it, which reinforces the need to incorporate mobile devices in the training process of students, using applications specially designed for this.